Effects of diet during pregnancy on placental efficiency in Holstein × Gyr Heifers - Oliveira, Kellen Ribeiro (2022)
Placenta and fetal growth depend of umbilical and uterine blood flow, and adverse conditions may impact the animal's entire life. This study aimed to evaluate the effects of diet during pregnancy on the blood supply to the placenta in two nutritional regimes throughout the gestational period, colostrum production, the newborn parameters and uterine involution. A total of fourteen Holstein × Gyr heifers with an average body weight of 446 kg ± 46.7 kg and age of 25 ± 3.9 mo were randomly assigned to the following treatments: moderate body weight gain (MOG, n = 7), the usual at tropical systems, where heifers were fed to achieve 0.5 kg/d of average daily gain (ADG); and high body weight gain (HIG, n = 7), where heifers to achieve 0.75 of ADG. The heifers received the same diet with corn silage and a concentrate-based diet twice daily varying the dry matter (DM) according to ADG, adjusted each 28 d of each treatment until calving. The placentome vascularization was assessed by using a Color-Doppler ultrasound. After calving, cotyledon was sampled to analyze mRNA expression of genes involved in angiogenesis process in the placenta. After birth, calves were weighed, received colostrum, and had their efficiency of transfer of passive immunity (TPI) assessed. The MOG heifers had a greater number of cotyledons (81.5 ± 12.9 vs. 63.6 ± 10.5), and continuous growing in placentome vascularization compared to HIG heifers. Indeed, MOG heifers had a greater the mRNA expression of VEGFB and IGFR1, as well as estradiol concentration before calving compared to HIG heifers. On the other hand, a greater colostrum production was observed in HIG heifers (3.94 ± 1.05 vs. 2.18 ± 1.57), but with lower quality (25.2 ± 0.51 vs. 29.5 ± 0.65; Brix %). Further, postpartum serum calcium and glucose were greater on d 8 in MOG heifers, but an equal immune response and uterus involution. The calf from HIG heifers had a better vitality score and equal body weight (BW) at birth and efficiency in TPI. Collectively, our results show that moderate nutritional regimen during gestation of dairy heifers undergo maternal adaptations in the placenta to support gestation without damage to fetus and their postpartum life. Keywords: Cotyledon. Doppler ultrasound. Fetal programming. Gene expression